ANALISIS INDEKS HARGA SAHAM GLOBAL DAN INFLASI TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) - Dimas Ari Putra (2023)
The study aims to analyze the influence of the DJIA index in the United States, SSEC in China, N225 in Japan, and inflation in Indonesia on the movement of the IHSG (Indonesia Stock Exchange Composite Index) in the Indonesia Stock Exchange. The sample used in this study consists of monthly data for DJIA, SSEC, N225, and IHSG during the period from January 2019 to December 2022. The data analysis technique employed is Panel Data Regression Analysis using Eviews version 12 software with a significance level of 5%. The results of this study are as follows: (1) DJIA has an impact on the movement of IHSG in the Indonesia Stock Exchange, (2) SSEC influences the movement of IHSG in the Indonesia Stock Exchange, (3) N225 does not have an impact on the movement of IHSG in the Indonesia Stock Exchange, and (4) inflation affects the movement of IHSG in the Indonesia Stock Exchange. Keyword: DJIA, SSEC, N225, Inflation, and IHSG.